The Influence of Capital Structure, Profitability and Company Size on Company Value at PT Kalbe Farma Tbk for the 2007-2022 Period - Aziziah, Aina (Indonesian Financial Review, 2024)
This research aims to determine the influence of capital structure, profitability, and company size on company value (PBV) at PT Kalbe Farma Tbk for the 2007-2022 period. This research method uses quantitative methods that will be processed with the Eviews 12 SV application. The sample used is the financial report for the 2007-2022 period. Capital Structure shows a t-count value of -2.148 < t-table 2.145 and has a significance value of 0.0528 (0.0528 > 0 .05). Profitability (ROE) has a calculated t-value of 5.693 > t-table 2.145 and has a significance value of (0.0001 < 0.05). Company size (Total Assets) has a calculated t-value of 4.721 > t-table 2.145 and has a significance value of (0.0005 < 0.05). The results are influential and significant with a significance value of 0.000461 (0.000461 < 0.05) with a calculated f-value of 12.89326 > f-table 3.49 simultaneously.